The Influence of Leadership on Contract Employee Performance is Mediated by Commitment Organization - Sholiha, Ni'matus; Baskoro, Heru (Universitas Muhammadiyah Gresik, 2025)
Human Resource Management (HR) has a very important influence in optimizing the running of acompany. Leadership and organizational commitment are several factors that must be considered in orderto shape individual behavior that is able to increase employee performance productivity and achieveorganizational success. This research aims to prove that the influence of leadership on employeeperformance is mediated by organizational commitment. This research uses explanatory research. Thepopulation in this study was 83 CV contract employees. Jaya Prameswari. The sampling technique usespurposive sampling technique. Data collection uses questionnaires. The data analysis used in thisresearch is Partial Least Square (PLS) analysis. The research results show that leadership has a significantpositive effect on employee performance. Organizational commitment is able to significantly moderate theinfluence of leadership on employee performance with negative influences